Assessment of hydrocephalus in children based on digital image processing and analysis - Fabijańska, Anna; Węgliński, Tomasz; Zakrzewski, Krzysztof; Nowosławska, Emilia (Zielona Góra: Uniwersytet Zielonogórski)
Hydrocephalus is a pathological condition of the central nervous system which often affects neonates and young children. It manifests itself as an abnormal accumulation of cerebrospinal fluid within the ventricular system of the brain with its subsequent progression. One of the most important diagnostic methods of identifying hydrocephalus is Computer Tomography (CT).
Keywords: hydrocephalus; computed tomography; image segmentation; Evans index; frontal and occipital horn ratio; ventricular angle; frontal horn radius